KCNK3: new gene target for pulmonary hypertension?. (August 2014) - Girerd, Barbara; Perros, Frédéric; Antigny, Fabrice; Humbert, Marc; Montani, David
<x xml:space="preserve">Abstract</x> Recently, KCNK3 has been identified as a new predisposing gene for pulmonary arterial hypertension (PAH) by whole-exome sequencing. Mutation in KCNK3 gene is responsible for the first channelopathy identified in PAH. PAH due to KCNK3 mutations is an autosomal dominant disease with an incomplete penetrance as previously described in PAH due to BMPR2 mutations. This discovery represents an important advance for genetic counselling, allowing identification of high risk relatives for PAH and possible screening for PAH in KCNK3 mutation carriers.